Analisis Komunikasi Organisasi di Era Digital dan Dampaknya Terhadap Masyarakat - Siti Karyati; Suwandi (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The transformation of organizational communication in the digital era significantly influences how organizations interact with the public. This study analyzes the fictional organization Sunda Empire as a case study to examine how digital organizational communication can shape public perception and create social impact. Using a descriptive qualitative approach based on literature studies and online documentation, the research finds that uncontrolled digital communication can lead to the spread of hoaxes, the creation of misleading organizational images, and negative effects such as confusion, fraud, and psychological harm to society. Low digital literacy exacerbates these effects. The findings emphasize the importance of improving digital literacy, enforcing regulations on illegal organizations, and educating the public about responsible technology use. Collaboration between the government and the community is essential to prevent the destructive consequences of fictitious organizational communication in the digital age